Classification Implementation Model Class Students In Parallel In SD Muhammadiyah 8 Jagalan Class V Academic Year 2016/2017 - Sulistyaningsih, Sulistyaningsih, Honest Umi Kaltsum, SS., M.Hum (2017)
Schools are the formal education to the learners that quite a lot and have the capabilities, characteristics and interests of the differents. The way to overcome the differences in the characteristics of learners, is grouping students, that have similar characteristics or almost the same. This study aims to 1) describe the implementation model of grouping students in parallel classes in SD Muhammadiyah 8 Jagalan, 2) identifying the positive impact of grouping for students, 3) identify the negative impact grouping for students as well as solutions to minimize the negative impacts of the grouping. The research is a qualitative research with descriptive research design. Techniques of collecting data using interviews, observation, and documentation. The validity of the data using a triangulation of sources and methods. The analysis techniques of data is done interactively covering reduction, presentation, and drawing conclusions. The conclusion of the study: (1) Grouping learners VA classes grouped by ability level of knowledge, class V B and C simply divided into two classes. (2) The positive impact of grouping for students is the fulfillment of learning facilities and students feel comfortable when the following learning activities in the classroom. (3) The negative impact of the grouping is there are some parents do not approve the grouping of students based on their level of knowledge. The solution is to provide insight to parents that the child's intelligence is not limited to the intelligence of knowledge alone. Students with low ability students conceptualized as less intelligent. The solution is not to tell children that they are grouped by ability level of knowledge. Lack of motivation to compete in a class with low ability. The solution teacher must continue to support the activities of learners and provide optimal learning facilities to students.